OP9 Single Cell RNA-sequencing reveals novel targets with a potential role in vascular regeneration in the ischaemic adult heart. (5th April 2020) - Solomonidis, Emmanouil G; Li, Ziwen; Meloni, M; Taylor, Richard S; Duffin, R; Dobie, R; Magalhaes, Marlene S; Louwe, Pieter A; D'Amico, Gabriela; Hodivala-Dilke, Kairbaan M; Mills, Nicholas L; Simons, Benjamin D; et al.
Abstract : Ischaemic heart disease remains a leading global cause of death. Restoring blood perfusion in the peri-infarct border region may limit further infarct expansion and promote cardiac regeneration. However, the pathways driving endogenous vascular regeneration following myocardial infarction (MI) remain poorly understood. We aimed to investigate the origin, clonal dynamics and transcriptional profiles of resident coronary endothelial cells (EC) in the post-ischaemic adult mouse heart and to apply single cell RNA-sequencing (scRNAseq) to identify and validate novel targets with a potential role in neovasculogenesis following MI. MI was induced in an EC-specific multispectral lineage-tracing mouse, ' Pdgfb-iCreERT2-R26R-Brainbow2.1 ' by permanent ligation of the left anterior descending coronary artery. Blood vessel formation via clonal proliferation by resident coronary vascular EC was significantly upregulated in the ischaemic border at 7 days post-MI, compared to the healthy heart (Pdgfb-Confetti+ EC per clone = 4.0 ± 2.1 versus 10.3 ± 10.6, P<0.0001). ScRNAseq analyses revealed 10 transcriptionally discrete heterogeneous EC states in the ischaemic heart and revealed molecular pathways through which each cluster was likely to mediate neovasculogenesis following MI. Plasmalemma vesicle–associated protein (Plvap) gene expression was upregulated in MI in a cluster specific manner, indicating its potential relevance to neovasculogenic pathways. We further showed that PLVAP protein expression was EC-specific and significantly greater in the infarct border of the post-ischaemic mouse heart compared to the healthy heart (% PLVAP+ EC = 70.5 ± 19.9% versus 38.7 ± 28.2%, P=0.002). PLVAP expression was also significantly increased in EC adjacent to regions of fibrosis and scarring in the ischaemic human heart, compared to healthy human hearts (% PLVAP+ EC = 36.9.8 ± 10.1% versus 12.7 ± 12.1%, P=0.02). Moreover, in vitro silencing using RNAi in HUVECS showed that PLVAP plays a role in regulating EC proliferation (% EdU+ HUVEC = 60.7 ± 3.9% versus. 21.1 ± 11.0%, P = 0.0038). In summary, we present a single cell gene expression atlas of cardiac resident EC, which can be interrogated to define the transcriptional profile of post-MI ECs and subsequently identify novel targets, such as PLVAP, with a potential role in augmenting endogenous myocardial perfusion following ischaemia.